Chemical composition of three Xylopia leaf essential oils from Pasoh Forest Reserve, Negeri Sembilan, Malaysia - Ab Ghani, Siti Humeirah; Mohamad Ali, Nor Azah; Jamil, Mailina; Hamid, Muhajir; Abdullah, Mohd Puad (Forest Research Institute Malaysia, 2010)
Hydro distillation of the leaves of Xylopia malayana, X. fusca and X. elliptica collected from Pasoh Forest Reserve, Negeri Sembilan, Malaysia yielded 1.39, 1.25 and 0.56% (v/w) of pale yellow and yellowish oils respectively. The chemical compositions of the oils were analysed by gas chromatography (GC) and gas chromatography mass spectrometry (GCMS). A total of 29 (94.4% of the total oil), 22 (78.8%) and 34 (80.7%) compounds were identified from essential oils of the leaves of X. malayana, X. fusca and X. elliptica respectively. Analyses of the oils revealed that the main components from X. malayana leaf oil were β-pinene (42.0%), α-pinene (15.2%), elemol (11.6%) and bicyclogermacrene (5.2%) whilst the principal components of the X. fusca leaf oil were germacrene D (17.0%), bicyclogermacrene (12.0%), β-elemene (11.5%) and β-pinene (10.1%). Major compounds of X. elliptica leaf oil were bicyclogermacrene (11.5%), sabinene (10.6%), α-pinene (9.0%), elemol (8.1%) and β-pinene (5.4%).